(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Devkota RP, Subedi JR, Wagley K. 2021. Prevalence of gastrointestinal parasites in equines of Mustang District, Nepal. Biodiversitas 22: 3958-3963. The study was conducted from March 2018 to November 2018 in four villages of Mustang district to find out the prevalence of gastrointestinal parasites in equines (horses and mules). Fecal samples collected from 175 randomly selected equines (105 from horses and 70 from mules) were preserved in 2.5% potassium dichromate and microscopically examined using concentration techniques to detect ova, larvae, and oocysts of parasites. The overall prevalence of gastrointestinal parasites was found to be 84.57% with an incidence rate of 81.90% and 88.57% in horses and mules respectively. The prevalence of gastrointestinal parasites between horses and mules did not vary significantly (p>0.05). Also no significant association (p>0.05) between the prevalence rate of parasites and study areas was observed. Among identified parasites in horses, Strongyles showed the highest prevalence (68.57%) followed by Strongyloides spp. (23.80%), and Parascaris equorum (14.28%) and in mules Strongyles showed the highest prevalence (80.0%) followed by Parascaris equorum (35.71%), Strongyloides spp. (28.57%), and Dictyocaulus spp. (5.71%). Prevalence of gastrointestinal parasites showed no significant variation (p>0.05) with respect to age and feeding status. However, the prevalence rate significantly varied (p<0.05) with respect to parameters like infection status (single and mixed), housing condition and health status. The present study revealed a higher prevalence rate of gastrointestinal parasites due to poor husbandry practices and lack of adequate veterinary services. Therefore, improvement in housing and feeding system, awareness regarding effective regular deworming, and establishment of veterinary hospitals in the study areas were recommended.